Gambaran Luaran Fungsional Tatalaksana Pasien Neglected Fraktur Sub-trokanter Menggunakan Reversed Distal Femur Limited Contact Dynamic Compression Plate di Rumah Sakit Bhayangkara Manado - Rifai, Lilik; Rawung, Rangga B. V.; Wagiu, Angelica (Universitas Sam Ratulangi, 2021)
Abstract: Subtrochanter fracture is still a health problem due to the difficulty of treatment and the high incidence of non-union and malunion after treatment. Limited Contact-Dynamic Compression Plate (LC-DCP), an implant designed to be used in distal femur fractures, is reported as an alternative for the treatment of subtrochanter fractures. This study was aimed to obtain the functional outcome of neglected subtrochanter fractures using reversed distal femur LC-DCP at Bhayangkara Hospital Manado. This was a retrospectoive study using the medical record and by-phone evaluation of patients with neglected subtrochanter that were managed with the reversed distal femur LC-DCP in 2018-2019 at Bhayangkara Hospital, Manado. Patients were evaluated with the Harris Hip Score (HHS). The results showed that there were 6 patients who met the inclusion criteria and could be contacted by phone. The HHS results showed 6 patients of poor category (mean score of 25.6) at 3 months after surgery; 3 patients of poor category and 3 patients of fair category (mean score of 66.4) at 6 months after surgery; and 4 patients of good category and 2 patients of excellent category (mean score of 89.9) at 12 months after surgery. In conclusion, the functional outcomes of the patients were poor category at 3 months after surgery, poor to fair at 6 months after surgery, and good to excellent at 12 months after surgery.Keywords: functional outcome, neglected subtrochanter fracture, reversed distal femur limited contact – dynamic compression plate, Harris hip score Abstrak: Fraktur subtrokanter masih merupakan masalah kesehatan karena sulitnya penanganan dan tingginya angka kejadian non-union dan malunion setelah penanganan. Limited contact-dynamic compression plate (LC-DCP) yaitu implan yang dirancang untuk fraktur femur bagian distal dilaporkan dapat dijadikan alternatif untuk penanganan fraktur subtrokanter. Penelitian ini bertujuan untuk memperoleh gambaran luaran fungsional tatalaksana pasien neglected fraktur subtrokanter menggunakan reversed distal femur LC-DCP di RS Bhayangkara Manado. Jenis penelitian ialah retrospektif menggunakan data rekam medis dan evaluasi melalui telepon pada pasien dengan neglected fraktur subtrokanter yang ditatalaksana menggunakan reversed distal femur LC-DCP pada tahun 2018-2019 di RS Bhayangkara Manado. Pasien dievaluasi dengan Harris Hip Score (HHS). Hasil penelitian mendapatkan 6 pasien yang memenuhi kriteria inklusi. Hasil evaluasi HHS mendapatkan 6 pasien kategori poor (rerata skor 25,6) saat 3 bulan pasca operasi; 3 pasien kategori poor dan 3 pasien fair (rerata skor 66,4) saat 6 bulan pasca operasi dengan; dan 4 pasien kategori good dan 2 pasien dengan kategori excellent (rerata skor 89,9) saat 12 bulan pasca operasi. Simpulan penelitian ini ialah luaran fungsional pasien-pasien tersebut ialah HHS poor pada 3 bulan pasca operasi; HHS poor-fair 6 bulan pasca operasi; dan HHS good-excellent pada 12 bulan pasca operasi. Kata kunci: luaran fungsional, neglected fraktur subtrokanter, reversed distal femur limited contact – dynamic compression plate, Harris hip score